2021
DOI: 10.1038/s41598-021-98551-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased burrow oxygen levels trigger defensive burrow-sealing behavior by plateau zokors

Abstract: Defensive behaviors are a response to immediate and potential threats in the environment, including abiotic and biotic threats. Subterranean rodents exhibit morphological and physiological adaptions for life underground, and they will seal with mounds and additional plugs when their burrow opened. However, little is known about the factors driving this defensive behavior. In this study, we selected a subterranean rodent, plateau zokor (Myospalax fontanieri), as a species to investigate (both in the laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Vitamin D deficiency leads to rickets in children and osteoporosis in adults, resulting in poor bone mineralization [ 5 ]. In nature, a variety of rodents such as the naked mole-rat, Damara mole-rat, and plateau zokor live entirely underground, which effectively shields them from sunlight, and feed on an herbivorous diet [ 31 , 32 , 33 ]. Previous studies have shown that the subterranean rodents Damara mole-rat and naked mole-rat have a natural vitamin D-deficient status [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency leads to rickets in children and osteoporosis in adults, resulting in poor bone mineralization [ 5 ]. In nature, a variety of rodents such as the naked mole-rat, Damara mole-rat, and plateau zokor live entirely underground, which effectively shields them from sunlight, and feed on an herbivorous diet [ 31 , 32 , 33 ]. Previous studies have shown that the subterranean rodents Damara mole-rat and naked mole-rat have a natural vitamin D-deficient status [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%